PENGARUH KETERGANTUNGAN ARTIFICIAL INTELLIGENCE TERHADAP KEMANDIRIAN AKADEMIK MAHASISWA DI FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI MEDAN - Jeta Amina Siahaan; Sitti Subaedah; Fira Aprilia; Esabella Sinaga; Sentia Br.Malau; Agnes Ginting; Karolin Stefani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of dependence on Artificial Intelligence (AI) on students' academic independence. The rapid development of AI technology in the era of digital transformation has significantly influenced learning behavior in higher education. While AI provides efficiency and accessibility in academic activities, excessive use may lead to dependency, potentially reducing students’ critical thinking and self-regulated learning abilities. This study employed a quantitative approach with an ex post facto correlational design. The sample consisted of 33 students from the Faculty of Education, Universitas Negeri Medan. Data were collected using a Likert-scale questionnaire and analyzed through descriptive statistics and simple linear regression. The findings reveal a significant negative relationship between AI dependency and academic independence. The higher the level of dependency on AI, the lower the students' ability to regulate their learning independently. These findings emphasize the importance of balanced and responsible AI usage in academic contexts to maintain students’ autonomy and critical thinking skills.